Sensing In/Security Sensors as transnational security infrastructures - Boker, Goeffrey C.; Poechhacker, Nikolaus; Klimburg-Witjes, Nina (Mattering Press, 2020)
This rich and extensive collection of studies examines sensors and sensing at the intersections of Critical Security Studies and Science and Technology Studies. Lucy Suchman, Lancaster University. Sensing In/Security is a book project that investigates how sensors and sensing practices enact regimes of security and insecurity. It extends long standing concerns with infrastructuring and emergent modes of surveillance and securitization by investigating how digitally networked sensors shape practices of securitization. Contributions in this volume engage with the ways in which sensing devices gain political and epistemic relevance in various forms of security, from border security and migration control to drone regulation, epidemiological tracking, aerial surveillance and hacking practices. Using infrastructure and infrastructuring as a conceptual lens, these studies explore the conditions of possibility of sensing threats and in/security, rendering multiple worlds tangible and (sometimes even more importantly) intangible. Instead of solely focusing on the specific sensory devices and their consequences, this collection engages with the emergence of sensor infrastructures and networks and the shaping of such 'macro entities' as international organizations, states and the European Union. This pre-print edition of Sensing In/Security contains the preface, the introduction and two empirical chapters. The full edited collection will be published with Mattering Press in Winter 2020. Please send an email to info@matteringpress.org to pre-order your copy, or if you want to review the final volume.